OPTIMASI HASIL KEDELAI DENGAN PENGGUNAAN LIMBAH PADAT PABRIK KELAPA SAWIT - Made Deviani Duaja; Elis Kartika; Gusniwati Gusniwati; Ferry Irawan (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2022)
Soybean is planted in some types of land agroecology, but production centers are mostly on peat and tides. This research was conducted at the soybean center in Rantau Rasau District with agroecology peat and tideland. The trial was arranged in a Randomized Block Design (RBD) with ten treatments and four times repeatitions. It consisted of several doses of organic material decanter cake (DC) and the percentage of the recommended amount of mineral fertilizer (RDF). RDF was selected based on Indonesia Food Crop Agriculture Service. Decanter cake from palm oil mill waste was used as a source of organic material. Experimental parameters are plant height, leaf number, grain yield, 100 grain weight, and the number of pods, seeds per pod, and plant. The result indicated the combination of mineral fertilizer and organic material DC had significant differences in increasing plant height and number of leaves. Different types of RDF and DC combinations showed substantial effects on the soybean yield and yield components. The combination of RDF 25% and decanter cake at any dose positively impacted soybean height, leaf number, and grain yield component. The highest dry seed yield of 2.48 tons per hectare was achieved by a combination of 25% RDF and 20 ton ha-1 decanter cake. Soybean yield in this study was higher than Anjasmoro’s description of 2.03–2.25 tons ha-1